High-performance work practices, employee well-being, and supportive leadership: spillover mechanisms and boundary conditions between HRM and leadership behavior - Hauff, Sven; Felfe, Jörg; Klug, Katharina (International journal of human resource management, 2022)
The aim of this paper is to deepen our understanding of the relationships between high-performance work practices (HPWPs) and employee well-being. In particular, we integrate three employee well-being types, proposing that HPWPs positively affect employee health (i.e. health status, sickness absence, and sleep quality), mediated by job satisfaction and employee engagement. We also analyze the influence of supportive leadership as a key contextual factor. We hypothesize that the positive relationships between HPWPs and employee health via job satisfaction and engagement will be reinforced by supportive leadership, since the relationships between HPWPs and a) job satisfaction and b) work engagement should be stronger when leadership is more supportive. These hypotheses are tested with representative data from German-speaking countries (Austria, Germany, and Switzerland; N = 3325). The results support the mediating roles of job satisfaction and work engagement. Interestingly, the remaining direct relationships between HPWPs and sleep quality are negative, which supports a counteracting effects model. We further find a moderating effect where, in contrast to our assumption, supportive leadership attenuates HPWPs' effects.